Astragaloside IV Inhibits Triglyceride Accumulation in Insulin-Resistant HepG2 Cells via AMPK-Induced SREBP-1c Phosphorylation - Wang, Chunyi; Li, Yan; Hao, Mengjiao; Li, Weimin (Frontiers in Pharmacology, 2018)
Objective: Insulin resistance is a risk factor for non-alcoholic fatty liver disease, which is characterized by lipid accumulation in hepatocytes. AMPK-induced SREBP-1c phosphorylation is crucial for proper regulation of lipid metabolism in the liver. Astragaloside IV (AST) was found to decrease lipid accumulation in hepatocytes by activating AMP-activated protein kinase (AMPK), which is required to regulate lipid metabolism in liver tissue by inducing SREBP-1c phosphorylation. Method: To evaluate the direct effect of AST on lipid accumulation in hepatocytes with insulin resistance and elucidate the underlying mechanisms, we induced insulin resistance in HepG2 cells, and used compound C and ACAIR (an AMPK inhibitor and agonist, respectively) as control substances. We evaluated glucose, triglyceride (TG), and non-esterified fatty acid (NEFA) production, as well as SREBP-1c transcription, SREBP-1c protein expression, and downstream gene expression with or without the presence of AST. We also investigated whether phosphorylation of SREBP-1c at Ser372 was required for AST function. Results: We found that AST attenuated insulin resistance and lipid accumulation in HepG2 cells. As an AMPK activator, AST promoted gene expression and activation of AMPK by increasing phosphorylation of AMPKa. AST also inhibited translocation of SREBP-1c into the nucleus of insulin resistant HepG2 cells by inducing phosphorylation of SREBP-1c at Ser372. Conclusion: This study demonstrated that AST attenuates insulin resistance and lipid accumulation in HepG2 cells by regulating AMPK-dependent phosphorylation of SREBP-1c at Ser372, suggesting AST as a promising drug for treating hepatic steatosis.